Impact of Active Control Turbocharging on the Fuel Economy and Emissions of a Light-Duty Reactivity Controlled Compression Ignition Engine: A Simulation Study - Bharath, Anand Nageswaran; Reitz, Rolf D.; Rutland, Christopher J. (Frontiers in Mechanical Engineering, 2021)
While forced induction strategies such as turbocharging can increase the power output and extend the load limit of engines operating on Low Temperature Combustion (LTC) strategies such as Reactivity Controlled Compression Ignition (RCCI), the low exhaust enthalpy prevalent in these strategies requires the use of high backpressures to attain high turbocharger efficiencies, leading to high pumping losses and in turn poor fuel economy. Hence there is a need to improve the exhaust energy utilization by the turbocharger such that the negative effects of the high backpressure requirements are offset. One turbocharger operating strategy that has the potential to enhance exhaust enthalpy conversion by the turbine is Active Control Turbocharging (ACT), in which the rack position of a Variable Geometry Turbocharger (VGT) is actuated using a continuously varying sinusoidal signal whose frequency is proportional to engine speed. In this study, the impact of ACT on turbocharger performance and fuel economy of a light-duty RCCI engine equipped with a VGT is investigated through coupled GT-POWER/KIVA-3V simulations at a medium-load cruise operating condition. A Design of Experiments (DoE) study was executed in which the rack position amplitude and phase angle were independently varied, and the turbine efficiency, compressor efficiency, crankshaft torque and Brake Specific Fuel Consumption (BSFC) were tracked for each run. The results show that ACT operation significantly increased the torque output while improving fuel economy over baseline VGT operation, but the range of actuation signal amplitude ratio was limited to 40% of the maximum amplitude possible due to peak cylinder pressure and peak pressure rise rate constraints. It is also shown that the impact of signal phase angle on turbocharger efficiency and overall system performance is not as significant as the amplitude ratio. The best fuel economy improvement over the baseline VGT operation at cruise conditions was observed at 40% amplitude ratio and 0° phase angle, and this value was 2.8%.